Proceedings of the SIGCHI Conference on Human Factors in Computing Systems 2013
DOI: 10.1145/2470654.2481315
|View full text |Cite
|
Sign up to set email alerts
|

Using an open card sort with children to categorize games in a mobile phone application store

Abstract: This paper presents a study aimed at better understanding how children categorize different games. The paper reports the results of an open card sort where participants were asked to categorize games from the Google Play Store (formerly the "Android Marketplace"). The key contribution of the paper is that when compared with existing categories in the Google Play Store, children used categorization criteria much more aligned to the goals of the game rather than more abstract categories currently found in mobile… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 14 publications
1
7
0
Order By: Relevance
“…Ebenezer 2003;Turnbow et al 2005). The broad applicability of the card sorting method is further demonstrated by studies involving children (Cassidy, Antani, and Read 2013;Pemberton and Road 2009), participants from different cultures (Petrie et al 2011) and varying literacy (Kodagoda, Wong, and Khan 2010).…”
Section: Card Sortingmentioning
confidence: 96%
“…Ebenezer 2003;Turnbow et al 2005). The broad applicability of the card sorting method is further demonstrated by studies involving children (Cassidy, Antani, and Read 2013;Pemberton and Road 2009), participants from different cultures (Petrie et al 2011) and varying literacy (Kodagoda, Wong, and Khan 2010).…”
Section: Card Sortingmentioning
confidence: 96%
“…If the number of children using application stores is significant, then it makes sense that we should be recognising children as users of app stores and considering their unique needs and wants in their design. Children categorise things differently to adults (Denney & Ziobrowski, 1972) and this has been seen with both books (Hutchinson, Druin & Bederson, 2007) and the categorisation of games within app stores themselves (Cassidy, Antani & Read, 2013). It was found children categorise games more in line with the characters in the game, what the character does within the game or the end goals of the game itself.…”
Section: Background and Related Workmentioning
confidence: 86%
“…This suggests children both discuss mobile phone games amongst their peers and also have a desire to discover games of their own, or games aligned to their friends interests. This raises an interesting question as to whether children find application stores intuitive to use, as prior research has shown the categories used in some application stores are not currently intuitive to younger children as they are too abstract (Cassidy, Antani & Read, 2013).…”
Section: Figure 1: Q4: Proportion Of Children Who Get Help From Parenmentioning
confidence: 99%
See 1 more Smart Citation
“…Different types of card activities have been used as methodological tools in many different research contexts: for example as 'thinking tools' aiding problem solving in design ideation [21], as a humancentered approach to addressing human values in design [19], to aid discussion of online privacy and consent [4], and to make IT law more accessible to citizens [40]. Cards have also been used to help designers to take account of the needs of children and young people, highlighting the importance of making sure materials are appropriate for the intended age group [5,10]. Ideation cards promote reflection on relevant issues, engaging a wide range of stakeholders, in particular non-experts, in generating ideas, promoting critical thinking, and allowing a focus on human values and users' needs [46].…”
Section: Engaging Young People In Researchmentioning
confidence: 99%